Unjuk Kerja Fuzzy Logic Static Synchronous Compensator (FLSTATCOM) untuk Meningkatkan Tegangan Sistem - Mataram, I Made (Majalah Ilmiah Teknologi Elektro; Vol 15 No 1 (2016): (January - June) Majalah Ilmiah Teknologi Elektro, 2016)
Abstract— The application of fuzzy techniques bring significant changes specific to calculation and analysis of conventional system. The application of FACTS (Flexible AC Transmission System) device have been improved the quality of voltage from the generator to the very large load. STATCOM is the most powerful equipment to improve the voltage on the electric power transmission network. The discussion in this study is devoted to FLSTATCOM. Fuzzy Logic models with two inputs is used as a controller IGBT, so as to improve the performance of conventional STATCOM. Single Machine Infinite Bus system into trial use FLSTATCOM. The result of simulation using MATLAB Simulink, the value of the voltage on each side received without using STATCOM generates a voltage of 217,3 kV, using STATCOM generates a voltage of 220.0 kV, and the use of FLSTATCOM able to increase the voltage became 228.9 kV ( 5.34 % ).
Keywords: Fuzzy Logic, STATCOM, Single Machine Infinite Bus, FACTS.